2011
DOI: 10.3171/2011.9.focus11187
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal nerve injury associated with sports-related knee injury

Abstract: Object This study analyzes 84 cases of peroneal nerve injuries associated with sports-related knee injuries and their surgical outcome and management. Methods The authors retrospectively reviewed the cases of peroneal nerve injury associated with sports between the years 1970 and 2010. Each patient was evaluated for injury mechanism, preoperative neurological status, electrophysiological studies, lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…4,5,10,15 Nearly onehalf of patients with nerve involvement may have a permanent deficit, and results of surgical repair have typically been modest, especially with longer grafts. 11,15,19,23,26,30 Increased prevalence of CPN palsy is associated with higher velocity injury mechanisms, 5,21 knee dislocations with posterior cruciate ligament and posterolateral corner injuries, 15 and increased BMI.…”
Section: Discussion Common Peroneal Nerve Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,10,15 Nearly onehalf of patients with nerve involvement may have a permanent deficit, and results of surgical repair have typically been modest, especially with longer grafts. 11,15,19,23,26,30 Increased prevalence of CPN palsy is associated with higher velocity injury mechanisms, 5,21 knee dislocations with posterior cruciate ligament and posterolateral corner injuries, 15 and increased BMI.…”
Section: Discussion Common Peroneal Nerve Injurymentioning
confidence: 99%
“…Common peroneal nerve (CPN) palsy has been reported in 25%-40% of cases. 4,5,10,15 The mechanism has been thought to be a stretch lesion to the posterolateral aspect of the knee. 24 Because of the broad zone of injury seen clinically, patients often fare poorly and do not recover either spontaneously or even when treated with long interpositional grafts.…”
Section: Neurosurg Focus 39 (3):e8 2015mentioning
confidence: 99%
“…Fifteen of 43 patients (35%) with a motor dysfunction of the common peroneal nerve in our study experienced a spontaneous improvement of symptoms within 1 year, and one patient experienced improvement even more than 1 year after the injury. Previous studies have demonstrated complete or partial recovery of nerve dysfunction in 40% to 50% of the patients [2,9,22,31]. It is known that a partial nerve lesion has a far better prognosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Sports are a relatively common cause of SPN entrapment. Cho et al [62] evaluated 448 cases of peroneal nerve injury; 84 cases (18%) were sports related included skiing (42 cases), football (23 cases), soccer (8 cases), basketball (6 cases), ice hockey (2 cases), track (2 cases) and volleyball (1 case). The other major cause of SPN entrapment is lateral (inversion) ankle sprains [63].…”
Section: Examples Of Nerve Entrapment Presenting As Crpsmentioning
confidence: 99%